Perspectives on Incorporating Background Information and Graph Presentation in Chemistry Laboratory Manual - Thimmappa, B.H.S. (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
Chemistry is a highly experimental science and the laboratory manual is an integral part of the curriculum. Laboratory work must be incorporated as a component element of a theory course in organic/inorganic chemistry to impart experimental skills. This paper presents the significance of incorporating background information and the basics of graphical presentation in the lab manual. It emphasizes the design of laboratory content to reflect the changes in the chemistry field.